Plants Neither Possess nor Require Consciousness. (August 2019) - Taiz, Lincoln; Alkon, Daniel; Draguhn, Andreas; Murphy, Angus; Blatt, Michael; Hawes, Chris; Thiel, Gerhard; Robinson, David G.
Abstract : In claiming that plants have consciousness, 'plant neurobiologists' have consistently glossed over the remarkable degree of structural and functional complexity that the brain had to evolve for consciousness to emerge. Here, we outline a new hypothesis proposed by Feinberg and Mallat for the evolution of consciousness in animals. Based on a survey of the brain anatomy, functional complexity, and behaviors of a broad spectrum of animals, criteria were established for the emergence of consciousness. The only animals that satisfied these criteria were the vertebrates (including fish), arthropods (e.g., insects, crabs), and cephalopods (e.g., octopuses, squids). In light of Feinberg and Mallat's analysis, we consider the likelihood that plants, with their relative organizational simplicity and lack of neurons and brains, have consciousness to be effectively nil. Highlights: Although 'plant neurobiologists' have claimed that plants possess many of the same mental features as animals, such as consciousness, cognition, intentionality, emotions, and the ability to feel pain, the evidence for these abilities in plants is highly problematical. Proponents of plant consciousness have consistently glossed over the unique and remarkable degree of structural, organizational, and functional complexity that the animal brain had to evolve before consciousness could emerge. Recent results of neuroscientist Todd E. Feinberg and evolutionary biologist Jon M. Mallatt on the minimum brain structures and functions required for consciousness in animals have implications for plants. Their findings make it extremely unlikely that plants, lacking any anatomical structures remotely comparable to the complexity of the threshold brain, possess consciousness.